Integration of Circular Economy in Environmental Accounting Practice: Opportunities and Challenges in the Green Economy Era - Daniel Andung Maloando SIMANJUNTAK; Jan WETAPO; Ida Bagus Awangga SUKMANTARA (Loka: Journal Of Environmental Sciences, 2024)
Purpose:Climate change, scarcity of natural resources, and increasing awareness of the importance of sustainability are driving a paradigm shift in economic and accounting practices. Circular economy, as an economic model that emphasizes resource efficiency through the principles of reuse, repair, and recycling, is becoming an increasingly relevant approach in the green economy era.Methodology:On the other hand, environmental accounting is developing as an important tool to measure, report, and manage the environmental impacts of business activities in a transparent and accountable manner. This article examines the opportunities and challenges in integrating the circular economy into environmental accounting practices based on a review of recent literature.Findings:The results of the study show that this integration not only supports the achievement of corporate sustainability but also strengthens strategic decision-making oriented towards environmental preservation and resource efficiency.Implication:There are various challenges, such as limited data, non-standard reporting standards, and organizational resistance, that need to be overcome to optimize the implementation of the integration.